Perlindungan Hukum dan Upaya Hukum terhadap Sengketa Penggunaan Merek Dagang Terdaftar (Studi Putusan PN Nomor: 2/Pdt.Sus.HKI/Merek/2022/PN.Niaga Sby) - Aurellia Cindy Puspitasari; Bagya Agung Prabowo (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
The brand is one form of the identity of a product that is marketed. In order to avoid the act of plagiarism toward a brand, the government already issued Law No. 20 of 2016 concerning Trademarks and Geographical Indications as a form of legal protection against brands. The purpose of this study is to find out the legal protection and legal attempts of registered brand disputes contained in court decision number 2/Pdt.Sus.HKI/Merek/2022/PN.NiagaSby Commercial Court in Surabaya between PS Glow and MS Glow. This study is a normative legal research that uses case and statute approaches. Data sources come from secondary data with data collection methods by library research and documentary research. The result of this study shows that legal protections for both registered brands that are disputing are related to the first-to-file principle that applies in Indonesia. The brand holders of PS Glow are entitled to obtain legal protection because it has a certificate based on Law No. 20 of 2016 concerning Trademarks and Geographical Indications. Meanwhile, the legal attempts which can be made by the registered brand holders towards the registered brand dispute are compensation claims through litigation if negotiation steps aren’t successful.